Legal Study on Boutique Hotels Law and Enhancement and Conservation of Environmental Quality Law for Sustainable Development of Grassroots Economy - Jaderojananont, Peerapon; Kittisaknawin, Chalermchai; Techaniyom, Kosin (Naresuan University Law Journal, 2025)
The purpose of this research is to examine legal difficulties and problems with Thai hotel law and environmental law that cause a conflict between the development of boutique hotels and the environmental protection. The study also applies a doctrinal legal research method, which concentrates on studying pertinent written legal sources together with qualitative research techniques, such as in-depth interviews and focus groups with stakeholders from both public and private sectors. This research finds that, the Thai hotel law and environmental law are essentially interconnected to encourage sustainable development concept. However, some of these laws’ provisions probably provoke legal defects and difficulties blocking boutique hotels to grow and to meet some environmental requirements as they require mostly particular characters different from other types of hotels. This is recommended that, therefore, Thai hotel law and environmental law should be partly amended to encourage the specific characters of boutique hotels in addition to promotion of collaboration between boutique hotels and their surrounding communities, enabling both of them to support each other in terms of local community development, social value and reducing environmental conflicts.